2019
DOI: 10.1021/acs.estlett.9b00085
|View full text |Cite
|
Sign up to set email alerts
|

Health Status of Elderly People Living Near E-Waste Recycling Sites: Association of E-Waste Dismantling Activities with Legacy Perfluoroalkyl Substances (PFASs)

Abstract: The elderly people living near electronic waste (e-waste) dismantling sites are susceptible to elevated chemical exposure, which is acerbated by hypometabolism and diminished immune tolerance. In this study, paired serum and urine samples collected from 1025 elderly people (≥60 years old) living near e-waste dismantling sites (n = 800) and reference areas (n = 225) in South China were analyzed for markers of health status and chemical exposures. Our results indicated that among all the health indicators fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Perfluoroalkyl substances (PFASs) are a major class of organic pollutants of increasing global concern that have become widespread as a result of their extensive use in common products and industrial applications, including firefighting foams and coatings, surfactants, lubricants, and as additives and byproducts of polymer production. , The total global amount of PFASs that have been produced to date is hundreds of thousands of tons. , PFASs are resistant to degradation, readily bioaccumulate, and thus persist in the environment. PFASs, including perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS), can be detected globally in air, water, soil, house dust, and many different marine and terrestrial organisms, including humans .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Perfluoroalkyl substances (PFASs) are a major class of organic pollutants of increasing global concern that have become widespread as a result of their extensive use in common products and industrial applications, including firefighting foams and coatings, surfactants, lubricants, and as additives and byproducts of polymer production. , The total global amount of PFASs that have been produced to date is hundreds of thousands of tons. , PFASs are resistant to degradation, readily bioaccumulate, and thus persist in the environment. PFASs, including perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS), can be detected globally in air, water, soil, house dust, and many different marine and terrestrial organisms, including humans .…”
mentioning
confidence: 99%
“…1,2 The total global amount of PFASs that have been produced to date is hundreds of thousands of tons. 3,4 PFASs are resistant to degradation, readily bioaccumulate, and thus persist in the environment. PFASs, including perfluorooctanoic acid (PFOA) and perfluorooctanesulfonic acid (PFOS), can be detected globally in air, water, soil, house dust, and many different marine and terrestrial organisms, including humans.…”
mentioning
confidence: 99%
“…Poly- and perfluoroalkyl substances (PFASs), such as perfluorooctanesulfonate (PFOS) and perfluorooctanoic acid (PFOA), have been widely detected in the environment and human bodies. Because of their extreme persistence and toxicity, PFOS and PFOA have been strictly regulated over the past several decades and have been replaced with short-chain PFASs in a number of industrial and commercial products. , In recent years, the ammonium salt of hexafluoropropylene oxide dimer acid (HFPO-DA), commonly known as GenX and used as a main substitute chemical for PFOA, has been under public scrutiny and has been the subject of several major lawsuits related to drinking water contamination. …”
Section: Introductionmentioning
confidence: 99%
“…As the number of cycles increases, the amount of TOC and COD reduced gradually, and after the fifth cycle, they are 0.13 and 15.08 mg/L, respectively. In this case, the discarded PSCs may cause an increase in oxygen consumption and may release CO 2 into the environment …”
mentioning
confidence: 99%
“…In this case, the discarded PSCs may cause an increase in oxygen consumption and may release CO 2 into the environment. 19 Overall, almost all the chemicals used in the fabrication of PSCs can readily leach out when subjected to water, rain, and landfill leachate. Results confirmed that Pb, the most concerning heavy metal in PSCs, can easily leach out even in DI water extraction.…”
mentioning
confidence: 99%